Flexible 3D laparoscopic assisted reduction and percutaneous fixation of acetabular fractures: Introduction to a new surgical option. Issue 10 (October 2016) - Mauffrey, C.; Hake, M.; Kim, F.J.
Abstract: The gold standard for fractures of the acetabulum is to perform an open reduction and internal fixation in order to achieve anatomical reduction. In a well-defined subset of patients, percutaneous techniques may be employed but achieving reduction by closed means can be challenging especially for fractures with large degrees of displacement. Such patient may include elderly patients who may not have the physiologic reserve to withstand open approaches. In our paper, we present a new option using laparoscopic assisted reduction of the acetabular fracture and percutaneous fixation. The young obese patient refused all forms of blood products transfusion and presented with a displaced transverse posterior wall fracture. While we do not recommend routine use of such technique and recognize its numerous limitations, we present it as an alternative strategy in a small subset of patients.